EFISIENSI ENERGI GUNA MENGURANGI KONSUMSI BAHAN BAKAR AKIBAT BIOFOULING PADA MT. KAKAP - Mutmainna; Sukirno; Ismail; Faisal Saransi (STKIP Subang, 2026)
Ship fuel consumption is influenced by hydrodynamic resistance, especially frictional resistance on the surface of the hull submerged in air. Biofouling attached to the ship's hull can increase the roughness of the ship's surface, increase resistance, and encourage increased fuel oil consumption (FOC). This study aims to analyze the effect of biofouling cleaning through docking on the fuel consumption of MT. Kakap and measure the magnitude of the decrease in FOC after hull cleaning. The study used a comparative quantitative approach with a case study design on one ship. The research data consisted of 30 pairs of daily FOC data, namely data before docking when the hull was coated with biofouling and data after docking after the hull was cleaned and re-coated with antifouling paint. Data analysis was carried out using descriptive statistics, the Shapiro-Wilk normality test, paired sample t-test, and simple linear regression. The results showed that the average FOC decreased from 10,144 tons/day to 7,883 tons/day after biofouling cleaning, with a decrease of 2,261 tons/day or 22.29%. The t-test results showed a significant difference between FOC before and after docking, while the regression results showed a relationship between ship hull condition and fuel consumption. These findings indicate that biofouling removal through docking contributes to increased operational energy efficiency, although fuel consumption remains influenced by other factors such as speed, draft, cargo condition, weather, and engine performance. This study recommends regular monitoring of hull conditions, evaluation of the effectiveness of cat antifouling, and control of ship operational variables to achieve more optimal fuel efficiency.